Leadership turnover, transaction costs and external city service delivery - Clingermayer, James C.; Feiock, Richard C. (1997)
Municipal service delivery decisions often generate considerable controversy and political turmoil. However, one aspect of political turmoil - turnover among leaders in city government - can also affect service delivery choices. Clingermayer and Feiock find that, in a number of local policy areas, turnover among mayors increases the probability of delivering services externally (i.e., through a private contractor, a nonprofit organization, or a different governmental unit). However, turnover among administrators reduces the likelihood of external service delivery for a number of services. - Reproduced
Keywords: Urban basic services - United States; Urban basic services; Local government